A case study on the influence of fitness trackers on older adults' health and fitness activities. (24th September 2021) - Enamela, Pranathy; Prybutok, Gayle L.; Dake, Jerry L.; Prybutok, Victor R.
This case study provides insight into older adults' motivation to improve their physical activity through the use of a fitness tracker. The study is qualitative and identified some of the obstacles related to adopting a healthy lifestyle including the need to modify dietary habits, expand knowledge of health-oriented decision making, and establishing exercise routines that are sustainable among older adults. The case study examined three professors over the age of 65. The participants had strong yet different perspectives towards personal health and fitness trackers. The key finding from this study is that wearables, especially fitness trackers, can significantly facilitate increased physical activity.